MEWUJUDKAN INSAN INDONESIA CERDAS KOMPREHENSIF DAN KOMPETITIF - Yulia Ayriza (Paradigma, 2006)
In the Opening (Preambule) of the 1945 Constitution, it has been stated that one of the Republic of Indonesia government’s goals is to smarten the national life. Thus, if the goal is achieved, then output obtained is intelligent Indonesian figures. The question needs to be forwarded is: What is actually the meaning of “intelligent”? Can education be said qualified if it just guide its pupils to be intellectually intelligent? In other words, what intelligent Indonesian Figures are expected by this country? The Department of National Education in the long term of the 2025 Strategic Plan about Building National Education mentioned that national education vision in 2025 wishes to yield intelligent, and Competitive Indonesian Figures. What meant by “intelligent” here is comprehensivelyintelligent, including spiritual, emotional and social, intellectual, and kinestetic intelligent (the Department of National Education, 2005).The national education vision can be achieved through long educationprocess at schools. As known that education is able to include bothacademic and non-academic education, so the development of the fourkinds of intelligence and competitive characteristic can be includedthrough education. Education strategy used can be done by meansmaking inclusive goal aspects that is going to be achieved into coconcentric curriculum. It means that education materials provided fromthe kindergarten up to the high school, even to university always containgoal aspects that are going to be reached and be increased graduallyboth in content and concentration in the higher education degree. Inaddition, it is necessary to pay attention that the institutionalization ofeducation goal aspects should be done as appropriate and balancewithout ignoring any roles of the aspects. In this matter, besides therelationships of inter-intelligence between physical one and spiritual onehad to be balance and mutually support, then the relationships of intraintelligence, that is, between spiritual one, emotional and social one, as well as intellectual one should be appropriate and balance.Keywords : comprehensively intelligent, competitive.